2017
DOI: 10.1016/j.cdtm.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating oxidized low‐density lipoprotein and atherosclerotic cardiovascular disease

Abstract: Atherosclerosis is a chronic, progressive disease which eventually leads to coronary heart disease (CHD), ischemic stroke and other atherosclerotic cardiovascular disease (ASCVD). Numerous studies have demonstrated an atherogenic role of oxidized low-density lipoprotein (ox-LDL) in the progression of ASCVD. This article briefly reviews the atherogenic mechanism of ox-LDL, the methods of measuring ox-LDL in the circulation, effect of medical therapy and life-style modification on ox-LDL level, and the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 52 publications
3
90
0
2
Order By: Relevance
“…In states of systemic inflammation like atherosclerosis and chronic infections, lipoproteins can be modified and get oxidized. Although many studies described the relation of LDLox and atherosclerosis, the impact of LDLox on atherogenesis remains unclear [29]. Unlike LDL, HDL is part of the innate immunity and also has the ability to influence cholesterol availability in lipid rafts in immune cells resulting in the modulation of toll-like receptors, MHC-II complex, as well as B-and T-cell receptors, while specific molecules shuttled by HDL such as sphingosine-1-phosphate (S1P) contribute to immune cells trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…In states of systemic inflammation like atherosclerosis and chronic infections, lipoproteins can be modified and get oxidized. Although many studies described the relation of LDLox and atherosclerosis, the impact of LDLox on atherogenesis remains unclear [29]. Unlike LDL, HDL is part of the innate immunity and also has the ability to influence cholesterol availability in lipid rafts in immune cells resulting in the modulation of toll-like receptors, MHC-II complex, as well as B-and T-cell receptors, while specific molecules shuttled by HDL such as sphingosine-1-phosphate (S1P) contribute to immune cells trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…DHA and EPA increased LDL particle size in hypertensive type 2 diabetes patients and with hypertriglyceridemia respectively, contributing to the protection against CVD [103,104]. Moreover, it was showed that omega 3 FA reduced circulating oxidized LDL and improved endothelial function in patients presenting a high risk for CVD [105][106][107]. Omega 3 FA directly replace proinflammatory omega 6 FA in biological membranes.…”
Section: Effects On Lipid Profilementioning
confidence: 99%
“…The mechanisms for the poor survival of transplanted BMSCs have not been fully understood and are very likely multifactorial including inflammation, oxidative stress, mechanical stress and hypoxia. Oxidized low‐density lipoproteins (ox‐LDLs) are naturally present in serum and an important source for reactive oxygen species (ROS) and oxidative stress . Ox‐LDL has been shown to inhibit proliferation and endothelial differentiation of BMSCs, and induce apoptosis of BMSCs with both ROS‐dependent and ROS‐independent mechanisms .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized low-density lipoproteins (ox-LDLs) are naturally present in serum and an important source for reactive oxygen species (ROS) and oxidative stress. 8,9 Ox-LDL has been shown to inhibit proliferation and endothelial differentiation of BMSCs, and induce apoptosis of BMSCs with both ROS-dependent and ROS-independent mechanisms. 10,11 Our previous study showed that ox-LDL impaired the survival of BMSCs in vitro partially through direct cell membrane damage independent of ROS formation.…”
Section: Introductionmentioning
confidence: 99%